2013
DOI: 10.1002/jmv.23530
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of complex mutational patterns in lamivudine resistant hepatitis B virus isolates

Abstract: The evolution of hepatitis-B virus (HBV) drug resistance is characterized by the emergence of resistance conferring mutations and compensatory mutations. Therefore HBV drug-resistant isolates often harbor multiple mutations in the reverse transcriptase (RT) and corresponding mutations in the hepatitis B surface antigen (HBsAg). In this study mutational patterns of 60 HBV isolates harboring drug resistance mutations rtM204V or rtM204I were retrospectively analyzed. Both mutations, especially mutation rtM204V, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
7
2
Order By: Relevance
“…This and other European studies showed that there was a mutational pattern bias of rtM204 V for HBV/A and rtM204I for HBV/D. 24,25 By contrast, no such bias was observed between HBV/B-and HBV/C-infected patients in our current study. In NA-untreated patients, drug-resistant mutations were detected in 2/140 (1.4%) of European patients with HBV/D.…”
Section: Discussioncontrasting
confidence: 72%
“…This and other European studies showed that there was a mutational pattern bias of rtM204 V for HBV/A and rtM204I for HBV/D. 24,25 By contrast, no such bias was observed between HBV/B-and HBV/C-infected patients in our current study. In NA-untreated patients, drug-resistant mutations were detected in 2/140 (1.4%) of European patients with HBV/D.…”
Section: Discussioncontrasting
confidence: 72%
“…It has been demonstrated that the main mutations associated with LAM-resistance are rtM204I and/or rtL180M, and these do not confer resistance to ADV [29,30]. The mutations associated with resistance ADV are mainly rtA181V and/or rtN236T [31].…”
Section: Discussionmentioning
confidence: 99%
“…M204 of reverse transcriptase YMDD motif), mutations related to immune escape in the HBsAg, and insertion/deletion mutants are selected for by NA therapies. [128][129][130][131][132][133][134][135][136][137] A recent study has quantitatively assessed selection of drug-resistant mutants in non-responders, by means of matrixassisted laser desorption-ionization time-of-flight mass spectrometry (MALDI-TOF MS). 138 It has been shown that drug resistance mutations can exist as minor or major variants prior to treatment, [139][140][141][142] and that existing mutations can influence the outcome of switching therapies.…”
Section: Quasi-species Antiviral Drug Resistance and Response To Na mentioning
confidence: 99%